The general budget in Libya and oil price fluctuations - الدامي بدر حسن (Dirasat in Economics and Business, 2024)
This study sought to analyze and measure the relationship between the dependence of the general budget in Libya on oil price fluctuations in its global markets during the period 1970-2016 - assuming its existence - since Libya is one of the countries whose economy depends primarily on the oil sector. The results of the analysis revealed that both sides of the general budget in Libya and its balance have witnessed development according to the fluctuations witnessed in oil prices. The results of the measurement supported by some statistical tests, confirmed the study’s hypothesis and indicated that this relationship was negative in the short run and positive in the long run.